THE INFLUENCE OF COUNTRY OF ORIGIN IMAGE, PRODUCT KNOWLEDGE AND PRODUCT INVOLVEMENT ON PURCHASING DECISIONS FOR NONGSHIN BRAND INSTANT NOODLES. - Mulia Sari; Nurainun (RADJA PUBLIKA, 2024)
The study aims to examine the effect of country of origin image, product knowledge and involvement on purchasing decisions for instant noodles Purchase. This study uses primary data obtained by distributing questionnaires to 105 respondents selected using the Hair et al. formula (2019). The data analysis method used is multiple linear regression method with the help of SPSS. The results of the study are that the image of the country of origin and product knowledge have no effect on purchasing decisions for Nongshin brand instant noodles, and product involvement has a positive and significant effect on decisions. The suggestion of this study is that if the company that contributes to the food industry, especially the Nongshin brand instant noodles, to be able to continue to innovate the product into the best product according to consumer needs.